Aggregate Analysis of the Impact of Cigarette Tax Rate Increases on Tobacco Consumption and Government Revenue : The Case of Indonesia - Djutaharta, Triasih; Viriya Surya, Henry; Pasay, N. Haidy A.; Hendratno; Adioetomo, Sri Moertiningsih (World Bank, Washington, DC, 2013)
This study uses aggregate times series data (annual data from 1970-2001) and monthly data from January 1996 to June 2001 to estimate the price and income elasticity of demand for tobacco products in Indonesia. Using various model specifications used in the cigarette demand literature, and then selecting the best model, it estimates the real price elasticity of cigarette demand as -0.345 and income elasticity of demand as 0.473. This inplies that a 10 percent real price increase would reduce consumption by 3.4 percent, and a 10 percent real income increase would raise consumption by 4.7 percent. The economic crisis after 1997 was found to increase consumption, over and above the effects of price and income, and the warning label on cigarette packs required after 1991 appears to have no significant impact on demand. Estimates based on the shorter period of monthly data showed less responsiveness to price and incomes, as would be expected. The study simulates the effects of a tax increase on total tobacco excise revenues and predicts that an increase in the tax level of 10, 50, or 100 percent would increase total tax revenue by 9 percent, 43 percent, and 82 percent respectively. The study comments on the effect of possible switching to cheaper products or illegal purchases.